Leaders and Negotiators: An Influence-based Metric for Rank - Ghosh, Rumi; Lerman, Kristina (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
We propose influence as a measure of the centrality of nodes in a network. Influence takes into account not only direct links but also all paths between nodes. We parametrize the influence metric by a variable alpha that measures the strength of links. Variations in rankings as alpha changes provides a mechanism to identify the central nodes within communities (leaders), as well as nodes that act as bridges between communities (negotiators).